ANALISIS YURIDIS TERHADAP PEMBATALAN DAN PENCABUTAN SERTIPIKAT HAK PENGELOLAAN YANG DIDALAMNYA TERDAPAT ALAS HAK KEPEMILIKAN ATAS TANAH ORANG LAIN (STUDI PUTUSAN NOMOR 37 PK/TUN/2013) - SOLI MEGAWATI HALAWA (PREMISE LAW JURNAL, 2016)
The problems of the research were what were the Judge’ considerations in settling the case in the Verdict of the PK (Judicial Review) No. 37 PK/TUN/2013, how the legal efforts of PT. Pelabuhan Indonesia I, and how the execution of the Verdict of the PK No.37 PK/TUN/2013 was. In order to find the answers to the problems, this research was descriptive analytical. The Judge’s considerations in the Verdict of the PK No.37 PK/TUN/2013 regarding the annulment and revocation of the certificate was in line with the procedure. The legal efforts that could be made by PT. Pelindo I (Persero) was applying for the establishment that the invalidation was nonexecutable, making remeasurement of the land and making resistance. The Verdict of PK No. 37 PK/TUN/2013 regarding the annulment and revocation of the certificate of Management Rights No.1/1993 belonging to PT.Pelindo I (Persero) could not be executed (non-executable). Keywords: Management Rights, Title, Annulmend and Revocation